(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Cost accounting and product cost calculation are key tools for effective management of a company’s financial and production processes. In the context of globalization, digitalization, and intensified competition, the requirements for accuracy, transparency, and flexibility of these processes are becoming increasingly relevant. This article examines the theoretical foundations of cost accounting, modern methods of cost calculation, international trends, and the specific features of applying these methods in the economy of the Kyrgyz Republic. Based on the analysis conducted, recommendations are provided to improve the efficiency of cost accounting under limited resource conditions.